SOSIALISASI IMPLEMENTASI KURIKULUM MERDEKA BERDASARKAN PROFIL PELAJAR PANCASILA - Yanti, Febri; Silalahi, Mastiur Verawaty; Situmorang, Masni Veronika; Sirait, Debora Exaudi; Siagian, Gunaria (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
Teachers at SD Negeri 064020 Medan have the problem of a lack of knowledge about implementing the independent curriculum, especially for the Pancasila student profile. Alternative solutions to the problems faced by teachers at SD Negeri 064020 Medan so that they can develop and increase their knowledge and can implement an independent curriculum at the school. By socializing it to teachers at SD Negeri 064020 Medan. The target outcomes that will result from the solution are: (1). Producing teachers who are able to increase knowledge and are able to implement an independent curriculum based on the Pancasila student profile, (2). The results of this program can later be published in national journals. After the socialization has been carried out to the teachers at State Elementary School 064020 Medan, the proposing team will carry out an evaluation by giving assignments and questionnaires to the teachers at State Elementary School 064020 Medan to fill in whether the results of the socialization have met the expected solution to the problems of the State Elementary School teachers. 064020 Medan. The aim of this activity is apart from being an effort by the Government to help the needs of the community, it also proves that the lecturers and HKBP Nommensen Pematangsiantar University are present and able to help with complaints and provide solutions to the community, especially teachers at SD Negeri 064020 Medan so that the vision of becoming a Superior and Competitive University is achieved as well as fulfilling the Tridharma Duties for Lecturers who provide community service.